Petrography and Mineralogy of Part of the Gold Schist Belt around Esa-Oke and Environs, Southwestern Nigeria - Falana, Olukayode Adeyinka (Mikailalsys Journal of Advanced Engineering International, 2025)
Esa-Oke, situated within the Ilesha Schist Belt of southwestern Nigeria, was the focus of this study aimed at conducting detailed geological mapping to identify geological structures, analyze the petrography of various rock types, determine the metamorphic facies, and evaluate the industrial potential of the rocks in the area. Field mapping facilitated the delineation of lithological units, textures, structural features, mineralogy, and modes of occurrence. Rock samples of granitic gneiss and quartzite were collected and analyzed petrographically through thin section preparation and examination under a petrographic microscope. Modal analysis of the granitic gneiss revealed the following mineral composition: Quartz (22.5%), Plagioclase (25.3%), Biotite (15.9%), Hornblende (8.4%), Microcline (15.2%), Sericite (0.6%), and Epidote (0.2%). The quartzite sample consisted predominantly of Quartz (90%), with Muscovite (6%) and Fibrolite (4%). Structural features such as foliation, joints, and folds were observed in both lithologies. Strike directions ranged from 02° to 71° (average: 32°), with dip trends of 45°E to 62°E (average: 46°E) and 22°W to 62°W (average: 40°W). Joint orientations ranged between 168° and 175°, with an average of 172°. The primary mineral assemblage in the granitic gneiss includes Quartz + Biotite + Microcline + Plagioclase + Hornblende, while secondary minerals include Sericite and Epidote. Quartzite is characterized by a mineral assemblage of Quartz + Muscovite + Fibrolite. These assemblages are indicative of amphibolite facies metamorphism. The petrographic and structural characteristics confirm that the area forms part of the Migmatite-Gneiss-Quartzite Complex of Nigeria. Both granitic gneiss and quartzite in the study area are suitable for use as construction aggregates, particularly in road construction.